Studi Literatur: Model Kooperatif tipe Make a Match Berbantuan Multimedia untuk Meningkatkan Minat dan Hasil Belajar - Belia Elga Saputri; Dewi Indrapangastuti (Universitas Sebelas Maret, 2025)
Interest skills and learning outcomes are very important to improve the academic success of elementary school students. The purpose of this study is to analyze the application of the Make a Match Model with the support of multimedia in increasing student interest and learning outcomes. The method used is a literature review study by collecting reference sources from relevant scientific research articles indexed in Google Scholar in the 2019-2025 period. The results of the study show that the application of the Make a Match model assisted by multimedia provides a responsive and enjoyable learning process, so that it can significantly increase students' interest in learning. This increase in interest has a good impact on student learning outcomes which also experience significant progress. The multimedia used is picture cards, and flipbooks that support the cooperative learning process. Thus, the integration of the Make a Match type cooperative learning model with multimedia is an effective and relevant approach to improving the interest and learning outcomes of elementary school students. Keterampilan minat dan hasil belajar sangat penting untuk meningkatkan keberhasilan akademik siswa sekolah dasar. Tujuan dari penelitian ini yaitu menganalisis penerapan Model Make a Match dengan dukungan multimedia dalam meningkatkan minat dan hasil belajar siswa. Metode yang digunakan adalah studi kajian literatur dengan pengumpulan sumber referensi dari artikel penelitian ilmiah yang relevan dan terindeks di Google Scholar pada rentang tahun 2019-2025. Hasil kajian memperlihatkan bahwa penerapan model Make a Match berbantuan multimedia memberikan proses pembelajaran yang responsif dan menyenangkan, sehingga mampu meningkatkan minat belajar siswa secara signifikan. Peningkatan minat ini berdampak baik terhadap hasil belajar siswa yang juga mengalami kemajuan secara signifikan. Multimedia yang digunakan adalah kartu bergambar, dan flipbook yang mendukung proses pembelajaran kooperatif. Dengan demikian, integrasi model pembelajaran kooperatif tipe Make a Match dengan multimedia menjadi pendekatan yang efektif dan relevan untuk meningkatkan minat dan hasil belajar siswa sekolah dasar.